Produtos e serviços de informação nas bibliotecas da UFPA: um estudo sobre a capacidade de uso por alunos do programa UNITERCI - CABRAL, Irlaneide Brito (2017)
The work is an analysis of the usability of products and services by participating students of the projects offered by the University Program of the Third Age (UNITERCI) of the Federal University of Pará (UFPA), which has its actions based on the university extension, offering activities social and digital inclusion for people from 55 years. Presents a case study of the use of mixed questionnaire containing four questions applied to ten of the twenty students of the project Body, Movement and Quality of Life in Old Age before enrolled in the Cultural Upgrade Project in the Third Age. Conducts a field survey to three UFPA libraries that were investigated the participation of these students in these spaces. With the application of the questionnaire and field research finds that low participation of the elderly in the UFPA information units and the lack of the same structure to meet their information needs.